2015
DOI: 10.1377/hlthaff.2015.0640
|View full text |Cite
|
Sign up to set email alerts
|

Improvements In US Diet Helped Reduce Disease Burden And Lower Premature Deaths, 1999–2012; Overall Diet Remains Poor

Abstract: Evaluation of time trends in dietary quality and their relation to disease burden provides essential feedback for policy making. We used an index titled the Alternate Healthy Eating Index 2010 to evaluate trends in dietary quality among 33,885 US adults. From 1999 to 2012, the index increased from 39.9 to 48.2 (perfect score = 110). Gaps in performance on the index persisted across socioeconomic groups or widened. Using data relating index scores to health outcomes in two large cohorts, we estimated that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 18 publications
(22 reference statements)
2
49
1
Order By: Relevance
“…Recent studies utilizing NHANES data showed that whereas overall dietary quality remains poor, there have been improvements to the quality of diet in America. [26][27][28] The increase in sedentary lifestyle could in part be responsible, as there has been a documented increase in sedentary lifestyle. 11,12 Sedentary lifestyle has been shown to negatively affect insulin sensitivity 29 and increase the relative risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies utilizing NHANES data showed that whereas overall dietary quality remains poor, there have been improvements to the quality of diet in America. [26][27][28] The increase in sedentary lifestyle could in part be responsible, as there has been a documented increase in sedentary lifestyle. 11,12 Sedentary lifestyle has been shown to negatively affect insulin sensitivity 29 and increase the relative risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inverse association observed between bean intake and BMI in this study suggests that increasing seasoning variety to increase intake of beans among urban Costa Rican adults may favorably affect obesity-related health outcomes. Among US adults, even small improvements in dietary quality are related to a reduced incidence of cardiovascular disease, type 2 diabetes, and cancer [36], and among Costa Rican adults, higher intake of beans has been shown to be associated with a healthy cardiovascular profile [8, 13]. In particular, Mattei et al [8] found that substituting one serving of beans for one serving of white rice would reduce the risk of metabolic syndrome by 35% in the same population, and meta-analyses suggests that an isocaloric increase of 1 serving per day of beans (typically in place of other dietary carbohydrate or animal protein) would reduce total and LDL cholesterol [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The medical and economic toll of this problem remains huge. It is estimated that the obesity epidemic carries a $117 billion medical price tag ( Wang, Li, Chiuve, Hu, & Willett, 2015).…”
Section: Consequences Of Juvenile Obesity and How It Affects Central mentioning
confidence: 99%